The Total Work of Art in European Modernism - Roberts, David, 1937- (Book collections on Project MUSE., 2011)
"In this groundbreaking book, David Roberts sets out to demonstrate the centrality of the total work of art to European modernism since the French Revolution. The total work of art is usually understood as the intention to reunite the arts into the one integrated whole, but it is also tied from the beginning to the desire to recover and renew the public function of art. The synthesis of the arts in the service of social and cultural regeneration was a particularly German dream, which made Wagner and Nietzsche the other center of aesthetic modernism alongside Baudelaire and Mallarme. The history and theory of the total work of art pose a series of questions not only to aesthetic modernism and its utopias but also to the whole epoch from the French Revolution to the totalitarian revolutions of the twentieth century. The total work of art indicates the need to revisit key assumptions of modernism, such as the foregrounding of the autonomy and separation of the arts at the expense of the countertendencies to the reunion of the arts; it cuts across the neat equation of avant-gardism with progress and deconstructs the familiar left-right divide between revolution and reaction, the modern and the antimodern. Situated at the interface between art, religion, and politics, the total work of art invites us to rethink the relationship between art and religion and art and politics in European modernism. In a major departure from the existing literature, David Roberts argues for twin lineages of the total work, a French revolutionary one and a German aesthetic one, which interrelate across the epoch of European modernism. These lineages culminate, Roberts shows, in the aesthetic and political radicalism of the avant-garde movements in response to the crisis of autonomous art and the accelerating political crisis of European societies from the 1890s forward."--Page 4 of cover.